Analisis Pancasila sebagai Landasan Hukum Anti Korupsi di Indonesia: Analysis of Pancasila as the Basis for Anti-Corruption Law in Indonesia - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Alfi Rosyidatul Ulfiyah; Aulia Nur Rohmah (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
Corruption is a problem that threatens the social, economic, and political foundations of Indonesia. This study analyzes the role of Pancasila as the legal foundation for anti-corruption efforts. As the state ideology, Pancasila contains moral, ethical, justice, and humanitarian values that are relevant to strengthening the fight against corruption. This qualitative research employs literature analysis, case studies, and interviews. The findings reveal that the five principles of Pancasila—Belief in One Almighty God, Just and Civilized Humanity, Unity of Indonesia, Democracy Guided by the Inner Wisdom of Deliberation and Representation, and Social Justice for All Indonesians—can serve as moral and ethical grounds for developing anti-corruption policies and regulations. The study highlights the importance of applying Pancasila values in education, public policy, and law enforcement to build a strong anti-corruption culture. With this holistic approach, Indonesia is expected to combat corruption both repressively and preventively, achieving justice and social welfare.